Declaring a tuberculosis outbreak over with genomic epidemiology. Issue 5 (31st May 2016) - Hatherell, Hollie-Ann; Didelot, Xavier; Pollock, Sue L.; Tang, Patrick; Crisan, Anamaria; Johnston, James C.; Colijn, Caroline; Gardy, Jennifer L.
Abstract : We report an updated method for inferring the time at which an infectious disease was transmitted between persons from a time-labelled pathogen genome phylogeny. We applied the method to 48 Mycobacterium tuberculosis genomes as part of a real-time public health outbreak investigation, demonstrating that although active tuberculosis (TB) cases were diagnosed through 2013, no transmission events took place beyond mid-2012. Subsequent cases were the result of progression from latent TB infection to active disease, and not recent transmission. This evolutionary genomic approach was used to declare the outbreak over in January 2015.